2017
DOI: 10.1002/14651858.cd002309.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 4 inhibitors for chronic obstructive pulmonary disease

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 66 publications
2
71
0
1
Order By: Relevance
“…Finally, targeted inhibition of other anti-inflammatory pathways to prevent AECOPD, the mechanism of action of the oral PDE-4 inhibitor roflumilast, has not been associated with increased pneumonia rates in clinical trials to date [Chong et al 2013;Yan et al 2014]. Also, in the large REACT trial, in which roflumilast was administered to patients with severe COPD already under treatment with LABA/ICS combination, there were no differences in the rate of pneumonia between the LABA/ICS + roflumilast group versus the LABA/ICS-only group [Martinez et al 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, targeted inhibition of other anti-inflammatory pathways to prevent AECOPD, the mechanism of action of the oral PDE-4 inhibitor roflumilast, has not been associated with increased pneumonia rates in clinical trials to date [Chong et al 2013;Yan et al 2014]. Also, in the large REACT trial, in which roflumilast was administered to patients with severe COPD already under treatment with LABA/ICS combination, there were no differences in the rate of pneumonia between the LABA/ICS + roflumilast group versus the LABA/ICS-only group [Martinez et al 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphodiesterase 4 highly expressed in inflammatory cells including neutrophils, macrophages, T cells and endothelial cells [38]. Insights from the respiratory system have shown that inhibition of phosphodiesterase 4 in immune cells and the subsequent elevation of cAMP results in an anti-inflammatory effect [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Insights from the respiratory system have shown that inhibition of phosphodiesterase 4 in immune cells and the subsequent elevation of cAMP results in an anti-inflammatory effect [38][39][40]. Specific inhibitors of this isoenzyme are being developed for use in the treatment of a wide range of disease states with an inflammatory component, including dermatological, neurological and respiratory conditions [38,[41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Cochrane review of 29 randomised controlled trials (15 trials with roflumilast and 14 trials with cilomilast), treatment with roflumilast compared with placebo was associated with a reduced likelihood of COPD exacerbation (odds ratio (OR) 0.77, 95% CI 0.71-0.83) [63]. The most common adverse effects are gastrointestinal in nature.…”
Section: Phosphodiesterase-4 Inhibitormentioning
confidence: 99%